Munasabah in Tafsir Irsyadul 'Amal (Study of Systematic Interpretation of Al-Qur'an Nuzul Surat Makkiyah Ibtidaiyah Period) - Reza Firmansyah; Iu Rusliana (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the concept of munasabah in Irsyadul 'Amal's interpretation. This research method is a qualitative type through literature study using content analysis. The results and discussion of this research include the meaning of munasabah, munasabah in the Al-Qur'an, and munasabah in the Tafsir of Irsyadul 'Amal. This research concludes that the development of munasabah is limited to the arrangement of the mushaf tartib, a new breakthrough recently discovered by the work of Tafsir Irsyadul 'Amal. In it applies the concept of munasabah which follows the systematic nuzul letter practically.